The forced air cooling heat dissipation performance of different battery pack bottom duct. (11th June 2018) - Xiaoming, Xu; Wei, Tang; Jiaqi, Fu; Donghai, Hu; Xudong, Sun
Summary: Due to the requirement of the battery for the thermal management system, based on the coupling relationship between the velocity field and the thermal flow field of the field synergy principle, the flow paths of the forced air cooling system for different battery packs were analyzed. First, the thermodynamic parameters of the battery were collected through experiments and verified by simulation. Secondly, based on the collected thermodynamic parameters of the battery, the heat generation model of the battery, the heat conduction model of the gas, and the coupled heat dissipation model of the battery and air were established. Determine the boundary conditions, calculation methods and evaluation indicators required for simulation; Finally, based on four different driving conditions, the forced air cooling performance of the double "U" shape duct and double "1" type duct is simulated. Through the analysis of the results, the dual "U" air ducts have a more heat dissipation effect on the battery pack than the double "1" shape duct. The results conform to the definition of the field synergy principle for the coupling relationship between the velocity field and the heat flow field. Then research provide references for the design of battery packs and matching of cooling systems.